2016
DOI: 10.1016/j.biopsych.2015.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the Oxytocin Receptor Gene Predicts Brain Region–Specific Expression and Social Attachment

Abstract: Background Oxytocin (OXT) modulates several aspects of social behavior. Intranasal OXT is a leading candidate for treating social deficits in autism spectrum disorder (ASD) and common genetic variants in the human oxytocin receptor (OXTR) are associated with emotion recognition, relationship quality and ASD. Animal models have revealed that individual differences in Oxtr expression in the brain drive social behavior variation. Our understanding of how genetic variation contributes to brain OXTR expression is v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
130
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 155 publications
(145 citation statements)
references
References 85 publications
14
130
1
Order By: Relevance
“…Moreover, a highly relevant study in rodents recently showed that a polymorphism in the Oxtr gene explains a large proportion of variance in accumbal OTR expression, which is known to be functionally relevant for attachment formation and parenting (King et al, 2015). A recent human study by Dannlowski et al (2015) identified an ELS-associated reduction in bilateral gray matter volume of the ventral striatum.…”
Section: Methodological Challenges Future Directions and Translatmentioning
confidence: 99%
“…Moreover, a highly relevant study in rodents recently showed that a polymorphism in the Oxtr gene explains a large proportion of variance in accumbal OTR expression, which is known to be functionally relevant for attachment formation and parenting (King et al, 2015). A recent human study by Dannlowski et al (2015) identified an ELS-associated reduction in bilateral gray matter volume of the ventral striatum.…”
Section: Methodological Challenges Future Directions and Translatmentioning
confidence: 99%
“…For example, recent research showed that genetic variations in the OT-receptor gene (OXTR) of prairie voles are related to social attachment and partner preference (King et al, 2015), and that knock-down of the OT receptor inhibited social attachment and parental care (Keebaugh et al, 2015). Also in human infants, polymorphisms in the OXTR gene have been associated with variations in attachment security (Chen et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…A burgeoning body of evidence highlights the role of several key genes within the oxytocin signaling pathway linked to sociability, including the oxytocin receptor gene (OXTR), CD38, and the structural gene for oxytocin (OXT) (4). Although mounting data strongly support the role of OXTR in the phenotypic expression of sociability in humans (5,6) and animals (7), the roles of other oxytocin pathway genes has received relatively little attention. As such, the role that OXT plays in the expression of sociability in humans is currently unknown.…”
mentioning
confidence: 99%